Benefits of musculoskeletal health promotion in school communities through service-learning: a mixed-method approach - Calvo, Sandra; Fortún-Rabadán, Rocío; Pérez-Palomares, Sara; Carpallo-Porcar, Beatriz; Lafuente-Ureta, Raquel; Jiménez-Sánchez, Carolina (Frontiers in Public Health, 2025)
BackgroundService-learning (S-L) is an educational method that enhances social and civic engagement among health science students, addressing unmet community needs. Musculoskeletal disorders (MSKD) represent a public health issue with increasing prevalence among school-aged population as reported by at least 1 on 5 children. Prevention programs for MSKD in schools are scarce, although evidence supports the efficacy of health education provided by physical therapists. This study aimed to evaluate the impact of a musculoskeletal health promotion program through S-L on school students, teachers, and physical therapy students.MethodsA mixed-methods approach was used. A quasi-experimental design assessed the learning and satisfaction of school students and teachers using pre-and post-intervention questionnaires. Additionally, qualitative data from reflective diaries of fourth-year physical therapy students were analyzed to capture their experiences. The intervention was conducted in 10 schools in Spain over two academic years, targeting children aged 10–14 and their teachers.ResultsA total of 1,051 school students and 32 teachers participated. Pre-post evaluations revealed significant learnings on MSKD prevention and body awareness in both groups (p < 0.05), highlighting the increase in knowledge about MSKD prevention and self-treatment for school students and on MSKD derived from inadequate postures for schoolteachers. Satisfaction was high, with students and teachers rating the program 4.4/5. Teachers highlighted the value of training for their professional practice, while students appreciated learning about self-care. Physical therapy students were 4 and reflected on their motivation for the project, learning experiences, as well as positive and negative aspects of the service.DiscussionThe S-L community-based intervention effectively increased awareness of musculoskeletal health and self-management skills. The peer learning environment and participatory approach encouraged engagement and knowledge retention in both students and teachers.ConclusionS-L is a valuable strategy for promoting musculoskeletal health in schools while improving health education skills among the future physical therapists through experiential learning.